1986
DOI: 10.1161/01.cir.74.3.501
|View full text |Cite
|
Sign up to set email alerts
|

Scintigraphic quantification of myocardial necrosis in patients after intravenous injection of myosin-specific antibody.

Abstract: The Fab fragments of antimyosin antibodies, labeled with 9mTc, were used in the scintigraphic examination of 30 patients with myocardial infarction. The ability to detect necrosis and determine its extent from the antimyosin scan were compared with the results of quantitative regional wall motion analysis by contrast ventriculography at 10 to 14 days and 99mTc-pyrophosphate imaging. Antimyosin images recorded by planar and single photon-emission computed tomography (SPECT) delineated areas of myocardial necros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0
1

Year Published

1989
1989
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(48 citation statements)
references
References 34 publications
(4 reference statements)
2
45
0
1
Order By: Relevance
“…One approach has been to radiolabel antibodies directed against diseasespecific epitopes. Radiolabeled monoclonal antibodies against myosin and major histocompatibility complex class II antigens have been used to detect myocardial infarction 15 and acute cardiac transplant rejection, 16 respectively. Atherosclerotic lesions in rabbits have been identified with radiolabeled antibodies or their Fab' fragments that bind to oxidized LDL 17 or proliferating smooth muscle.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…One approach has been to radiolabel antibodies directed against diseasespecific epitopes. Radiolabeled monoclonal antibodies against myosin and major histocompatibility complex class II antigens have been used to detect myocardial infarction 15 and acute cardiac transplant rejection, 16 respectively. Atherosclerotic lesions in rabbits have been identified with radiolabeled antibodies or their Fab' fragments that bind to oxidized LDL 17 or proliferating smooth muscle.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…Studies performed at 1-3 (n=97), [4][5][6][7][8][9][10][11] (n=39), [12][13][14][15][16][17][18][19][20][21][22][23] (n=46), and more than 24 months (n=65) showed a prevalence of abnormal antimyosin studies in each of the four periods of 95%, 77%, 65%, and 46%, respectively (p<0.0001) (Figure 2). In these periods, mean visual estimations were 1.95±0.7, 1.33±0.7, 1.15±0.7, and 0.9±0.7, and mean heart-tolung ratios were 1.93 +0.30, 1 In the 33 patients who were prospectively studied since transplantation, 170 antimyosin scans were sequentially performed (mean, 4.8±+ 1.9 scans per patient; range, 1-10 scans), and follow-up extended from 5 to 37 months (mean, 6 months).…”
Section: Antimyosin Studies In the Control Groupmentioning
confidence: 99%
“…In these periods, mean visual estimations were 1.95±0.7, 1.33±0.7, 1.15±0.7, and 0.9±0.7, and mean heart-tolung ratios were 1.93 +0.30, 1 In the 33 patients who were prospectively studied since transplantation, 170 antimyosin scans were sequentially performed (mean, 4.8±+ 1.9 scans per patient; range, 1-10 scans), and follow-up extended from 5 to 37 months (mean, 6 months). At 1-3 (n=96), [4][5][6][7][8][9][10][11] (n=38), [12][13][14][15][16][17][18][19][20][21][22][23] (n=24), and more than 24 months (n=12), prevalence of abnormal scans in each of the intervals was 95%, 76%, 58%, and 58%, respectively (p<0.0001). Mean values for visual estimation and heart-to-lung ratios in each of the intervals also decreased, to 1.95+0.7, 1.31+0.7, 1.08+0.8, and 0.9±0.9 and to 1.92+0.3, 1.72+0.23, 1.63+0.25, and 1.64+0.3, respectively (p<0.001).…”
Section: Antimyosin Studies In the Control Groupmentioning
confidence: 99%
“…Previous reports suggested that 99m-Tc localizes in severely injured but still viable myocardium early after reperfusion. 24 Therefore, we assume that 99m-Tc PYP uptake represents calcium overload within severely ischemic cardiomyocytes after reperfusion therapy. We also found that a better WM status or an improvement of MO segments at follow-up is accompanied by a decrease in the DE extent.…”
Section: Discussionmentioning
confidence: 99%